3D Printing: A Low Cost Desktop Electrochemical Metal 3D Printer (Adv. Mater. Technol. 10/2017). Issue 10 (10th October 2017) - Chen, Xiaolong; Liu, Xinhua; Childs, Peter; Brandon, Nigel; Wu, Billy
Abstract : Electrochemical additive manufacturing (ECAM) is a form of 3D printing that is able to create metallic structures without the need for high power lasers, metal powders or inert gas atmospheres. This is reported by Billy Wu and co‐workers in article number1700148 . The inside cover shows a new ECAM printer design using a meniscus confined approach which demonstrates volumetric printing speeds 3 orders of magnitude faster than equivalent systems.